2008
DOI: 10.1128/aac.01327-07
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Target Validation Studies of Aminopeptidase in Malaria Parasites Using α-Aminoalkylphosphonate and Phosphonopeptide Inhibitors

Abstract: During its intraerythrocytic phase, the most lethal human malarial parasite, Plasmodium falciparum, digests host cell hemoglobin as a source of some of the amino acids required for its own protein synthesis. A number of parasite endopeptidases (including plasmepsins and falcipains) process the globin into small peptides. These peptides appear to be further digested to free amino acids by aminopeptidases, enzymes that catalyze the sequential cleavage of N-terminal amino acids from peptides. Aminopeptidases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Its homologue, compound 19, bearing an additional methyl at carbon atom in position 3 also exhibited a significant activity against this enzyme. A similar model of activity was observed for the porcine aminopeptidases (Table 2) and aminopeptidase from Plasmodium falciparum (value of IC 50 for compound 18 is 22 lM; Cunningham et al 2008). This, alongside with significant activity of compound 21, indicates that there is a spacious binding site able to accommodate hydrophobic N-terminal fragments of inhibitors.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Its homologue, compound 19, bearing an additional methyl at carbon atom in position 3 also exhibited a significant activity against this enzyme. A similar model of activity was observed for the porcine aminopeptidases (Table 2) and aminopeptidase from Plasmodium falciparum (value of IC 50 for compound 18 is 22 lM; Cunningham et al 2008). This, alongside with significant activity of compound 21, indicates that there is a spacious binding site able to accommodate hydrophobic N-terminal fragments of inhibitors.…”
Section: Resultsmentioning
confidence: 54%
“…Aminopeptidase M17 prefers both aliphatic and aromatic hydrophobic aminophosphonates (compounds 18-20 and 1, 5 and 13; with analogues of leucine and homoalanine being of choice), whereas aminopeptidase M1 is preferably inhibited by aminophosphonates containing additional hydrophilic group in side chain, with analogue of homotyrosine (compound 24) being the most active. Although Plasmodium falciparum aminopeptidase M17 (EC 3.4.11.1) prefers aminophosphonates bearing hydrophobic aromatic moiety in their side chain (Cunningham et al 2008), the pattern of activity against this enzyme is also quite different because it is not sensitive to compounds 10-13. Thus, our study indicates that the use of libraries of simple inhibitors could be a useful tool in determining specificities of aminopeptidases and their fingerprints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cunningham et al 51 reported the evaluation of a series of α-aminoalkylphosphonate and phosphonopeptide inhibitors, designed against mammalian M17LAP, for their anti-malaria activity. They then correlated the IC 50 s of these compounds with their inhibitory activity against aminopeptidase activity in malaria cell extracts, and against recombinant PfM17LAP.…”
Section: 42mentioning
confidence: 99%